Economic and Psychological Approach to Increase Tax Compliance in Micro, Small And Medium Enterprises - Tri Utami; Susyanti Susyanti (Universitas Muhammadiyah Yogyakarta, Indonesia, 2018)
The objectives of this study are to examine the economic (perceived probability to audit and gain) and psychological (certainty, severity, social stigma, cynicism, guilty, the fairness of law) factors that influence tax compliance. The data from this study is obtained from the survey in 100 Micro, Small, and Medium Enterprises in Klaten Regency, who are affected by Government Regulation no. 46 Year 2013 regarding Final Income Tax for MSME possessing gross income less than IDR 4.8 billion per year. Multiple Regression analysis is used to test the hypotheses. The result shows that perceived probability to audit, stigma social and fairness of law are the factors that influence tax compliance positively.